Bio-Politics and Calculative Technologies in COVID-19 Governance: Reflections From England - Kelum Jayasinghe; Tarosha Jayasinghe; Chaminda Wijethilake; Pawan Adhikari (Kerman University of Medical Sciences, 2022)
Background  Through the extensive use of public media, the government of England was heavily involved in encouraging and instructing people on how to manage their life during coronavirus disease 2019 (COVID-19). This model of health emergency governance replicates the practice of 'calculative technologies' and 'bio-politics' embedded in population management. Previous research on COVID-19 governance both in the United Kingdom and beyond provides varied revelations on broader 'technologies of government' and bio-politics by numerous governments. However, rarely have any studies explicitly and distinctively highlighted the unique 'calculative technologies' mobilised by governments within their bio-politically designed "technologies of government" to compel the populations to manage their lives under their COVID-19 guidance. The paper therefor examines how the UK government deployed "calculative technologies," as part of its strategies of health governance and governmentality during the first wave of COVID-19 in England. Methods  This study uses document analysis as its data collection method. Its review includes documents, press releases, social media disclosures and health guidance issued by the UK government from March to December, 2020. The data are analysed employing the Foucault's governmentality and bio-political scholarship. Results  The paper's findings reveal the UK government's use of integrated calculative technologies of self-governance in the form of risk calculations and metrices/statistics (eg, death tolls, infection rates), performance management (eg, two metre social distancing, and hand washing for twenty seconds) and discipline and control (eg, fourteen days selfisolation), in addition to a more conventional top-down, managerial decision-making process adopted in the past. By these newly initiated "calculative technologies," the government has "bio-politically" governed the behaviours and lifestyles of vulnerable community members, health workers and general public at a distance, inculcating selfmanagement and individualisation of responsibility. Conclusion  The newly adopted calculative technologies used by the UK government created a multi-faceted discourse of obligations, entitlements and scale of engagement, and facilitated directions about what people should do to protect themselves and others from the spread of the virus. Overall, the overtly and idiosyncratically used calculative technologies resemble a unique 'art of government' and produce a set of 'bio-political' interventions enforcing the populations to manage their own wellbeing and governing them at a distance during COVID-19.